Surfactant modified clays’ consistency limits and contact angles (2012)
This study was aimed at preparing a surfactant modified clay (SMC) and researching the effect of surfactants on clays' contact angles and consistency limits; clay was thus modified by surfactants formodifying their engineering properties. Seven surfactants (trimethylglycine, hydroxyethylcellulose  octyl phenol ethoxylate, linear alkylbenzene sulfonic acid, sodium lauryl ether sulfate, cetyl trimethylammonium chloride and quaternised ethoxylated fatty amine) were used as surfactants in this study. The experimental results indicated that SMC consistency limits (liquid and plastic limits) changedsignificantly compared to those of natural clay. Plasticity index and liquid limit (PI-LL) values representing soil class approached the A-line when zwitterion, nonionic, and anionic surfactant percentageincreased. However, cationic SMC became transformed from CH (high plasticity clay) to MH (high plasticity silt) class soils, according to the unified soil classification system (USCS). Clay modifiedwith cationic and anionic surfactants gave higher and lower contact angles than natural clay, respectively.